Geometrically Constructed Families of Newton's Method for Unconstrained Optimization and Nonlinear Equations - Sanjeev Kumar; Vinay Kanwar; Sushil Kumar Tomar; Sukhjit Singh (International Journal of Mathematics and Mathematical Sciences)
One-parameter families of Newton's iterative method for the solution of nonlinear equations and its extension to unconstrained optimization problems are presented in the paper. These methods are derived by implementing approximations through a straight line and through a parabolic curve in the vicinity of the root. The presented variants are found to yield better performance than Newton's method, in addition that they overcome its limitations.